CinemaTexas notes : the early days of Austin film culture - Black, Louis, 1950-; Swords, Collins (University of Texas Press, 2018)
Austin's thriving film culture, renowned for international events such as SXSW and the Austin Film Festival, extends back to the early 1970s when students in the Department of Radio-Television-Film at the University of Texas at Austin ran a film programming unit that screened movies for students and the public. Dubbed CinemaTexas, the program offered viewers a wide variety of films--old and new, mainstream, classic, and cult--at a time when finding and watching films after their first run was very difficult and prohibitively expensive. For each film, RTF graduate students wrote program notes that included production details, a sampling of critical reactions, and an original essay that placed the film and its director within context and explained the movie's historical significance. Over time, CinemaTexas Program Notes became more ambitious and were distributed around the world, including to luminaries such as film critic Pauline Kael. This anthology gathers a sampling of CinemaTexas Program Notes, organized into four sections: "USA Film History," "Hollywood Auteurs," "Cinema-Fist: Renegade Talents," and "America's Shadow Cinema." Many of the note writers have become prominent film studies scholars, as well as leading figures in the film, TV, music, and video game industries. As a collection, CinemaTexas Notes strongly contradicts the notion of an effortlessly formed American film canon, showing instead how local film cultures--whether in Austin, New York, or Europe--have forwarded the development of film studies as a discipline.
Keywords: Motion pictures -- Texas -- Austin.; Motion pictures -- Texas -- History.; Culture in motion pictures.; Cinéma -- Texas -- Histoire.; Culture au cinéma.; Cinéma -- Texas -- Austin.; PERFORMING ARTS -- Reference.; PERFORMING ARTS / Film & Video / History & Criticism; Culture in motion pictures; Motion pictures; Texas; Texas -- Austin; Electronic books.; History